Linc-GALMD1 Regulates Viral Gene Expression in the Chicken - He, Yanghua; Han, Bo; Ding, Yi; Zhang, Huanmin; Chang, Shuang; Zhang, Li; Zhao, Chunfang; Yang, Ning; Song, Jiuzhou (Frontiers in Genetics, 2019)
A rapidly increasing number of reports on dysregulated long intergenic non-coding RNA (lincRNA) expression across numerous types of cancers indicates that aberrant lincRNA expression may be a major contributor to tumorigenesis. Marek’s disease (MD) is a T cell lymphoma of chickens induced by Marek’s disease virus (MDV). Although we have investigated the roles of lincRNAs in bursa tissue of MDV-infected chickens in previous studies, the molecular mechanisms of lincRNA functions in T cells remain poorly understood. In the present study, Linc-GALMD1 was identified from CD4+ T cells and MSB1 cells, and its expression was significantly downregulated in MD-resistant line of birds in response to MDV challenge. Furthermore, loss-of-function experiments indicated that linc-GALMD1 significantly affected the expression of 290 genes in trans. Through integrated analysis of differentially expressed genes (DEGs) induced by MDV and linc-GALMD1, we found that IGLL1 gene expression levels had a positive correlation with the degree of MD infection and could potentially serve as an indicator for clinical diagnosis of MD. Moreover, an interaction between MDV and linc-GALMD1 was also observed. Accordingly, CEF cells were inoculated with MDV with and without the linc-GALMD1 knockdown, and the data showed that linc-GALMD1 could repress MDV gene expression during the course of MDV infection. These findings uncovered a role of linc-GALMD1 as a viral gene regulator and suggested a function of linc-GALMD1 contributing to tumor suppression by coordinating expression of MDV genes and tumor-related genes and regulating immune responses to MDV infection.